Sedation of the trauma patient in the intensive care unit - Joseph, Anna (Journal of Emergency and Critical Care Medicine; Vol 2 (January 2018): Journal of Emergency and Critical Care Medicine, 2018)
Sedation in the intensive care unit (ICU), in the United Kingdom known as the intensive therapy unit or ITU has evolved from what was essentially an extended general anaesthetic, where patients were heavily sedated and often fully paralysed with neuromuscular blocking drugs to an evidenced based, multidisciplinary concept of care. The underlying tenets of good sedation practice have not changed- the relief of pain, anxiety and agitation, the need for tolerance of ICU interventions and nursing care and the management of delirium. What has changed is our approach in light of studies looking at the short and long term outcomes in trauma patients who require ICU treatment. It is now apparent that heavy sedation can be harmful, and as such sedation has become a more complicated and multifaceted issue. This review will look at the most commonly used ICU sedatives and how to develop a sedation strategy for the trauma patient based on the interplay between the factors necessitating sedation, namely pain, agitation and delirium. Consideration is given to alternative treatments to reduce sedation such as control of the ICU environment and alternative pharmacological therapies.